Poverty, Parent Involvement, and Children's Reading Skills: Testing the Compensatory Effect of the Amount of Classroom Reading Instruction. Issue 7 (3rd October 2021) - Gay, Brittany; Sonnenschein, Susan; Sun, Shuyan; Baker, Linda
ABSTRACT: Research Findings : Parent involvement is a critical way for children to learn about the importance of education and develop reading skills. Unfortunately, not all low-income parents are able to be involved in their children's education, which can have negative implications for children's reading development. The present study tested if the strength of the relation between low-income parents' involvement and children's reading skills in first grade varied by the amount of classroom reading instruction that children received at school. This study used data from the Early Childhood Longitudinal Study – Kindergarten: 2010–2011 (ECLS-K: 2011) to examine the relations between low-income parent involvement in education, amount of classroom reading instruction, and first-grade children's reading skills. Parent involvement was significantly more impactful for children who received less than 2 hours of classroom reading instruction. Additionally, children from poor households scored lower, on average, on reading assessments than children from near-poor households. Practice or Policy : Parent involvement has a positive impact on children's reading skills, but that impact can be contingent on what occurs within the classroom. This study underscores the need to consider both home and school influences on children's reading skills. Implications for educational practice and policy are discussed.